2017
DOI: 10.1002/pssa.201700493
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Strength of Dislocations in High‐Performance Multicrystalline/Quasi‐Mono Hybrid Wafers During Solar Cell Processing

Abstract: Wafers from a hybrid silicon ingot seeded in part for High Performance Multicrystalline, in part for a quasi‐mono structure, are studied in terms of the effect of gettering and hydrogenation on their final Internal Quantum Efficiency. The wafers are thermally processed in different groups – gettered and hydrogenated. Afterwards, a low temperature heterojunction with intrinsic thin layer cell process is applied to minimize the impact of temperature. Such procedure made it possible to study the effect of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…RAGB's were also investigated by SIMS, but the enrichment characteristic of dislocation clusters was not found here. Further details of this study are published elsewhere .…”
Section: Resultssupporting
confidence: 56%
“…RAGB's were also investigated by SIMS, but the enrichment characteristic of dislocation clusters was not found here. Further details of this study are published elsewhere .…”
Section: Resultssupporting
confidence: 56%
“…A detailed description of the seeding structure can be found elsewhere. 8,16 More information about wafer processing and sample preparation can also be found therein, but the basic details are presented below.…”
Section: A Growth and Processingmentioning
confidence: 99%
“…3,7 It was reported that the increased recombination strength of dislocations during solar cell processing can be related to a change in precipitate distribution. 8 In the so-called High Performance Multicrystalline (HPMC) silicon, material grain boundaries are an important part of the structure. Traditionally, grain boundaries were considered as harmful to device performance, and crystal growth processes were optimized to obtain large grains with small grain boundary densities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the recombination activity of dislocations can be quantified from the IQE maps. [9][10][11][12][13] For grain boundaries, the approach is typically based on the contrast profile of individual grain boundaries, i.e., the linescan contrast between the current induced by either an electron beam or a light beam at the grain boundary and the background current value. [14][15][16][17][18][19][20] Although such an approach is extremely useful in understanding the behavior of individual grain boundaries, it may be difficult to obtain an overall assessment of the impact of grain boundaries on the performance of the solar cell based on a few isolated grain boundaries.…”
Section: Introductionmentioning
confidence: 99%